Acquired vulnerability against EGF receptor inhibition in gastric cancer promoted by class I histone deacetylase inhibitor entinostat - Tamara Zenz; Robert Jenke; Denys Oliinyk; Sandra Noske; René Thieme; Tim Kahl; Ines Gockel; Florian Meier-Rosar; Achim Aigner; Thomas RH Büch (Neoplasia: An International Journal for Oncology Research)
Introduction: Histone deacetylase inhibitors (HDACi) have shown promising preclinical activity in gastric cancer cells; unfortunately, however, these could not be confirmed in clinical trials. This highlights the need for the identification of underlying reasons, which may also provide the basis for possible combination therapies. Here, we delineated the effects of HDACi on components of EGFR signalling in gastric cancer cells. Methods: We investigated entinostat effects on EGFR and amphiregulin (AREG) expression in various cell line- and primary patient tumor-based in vitro, ex vivo and in vivo models, on the mRNA and protein level. Based on these results, a combined entinostat plus EGFR inhibitor erlotinib treatment in vitro and in vivo was studied. Results: Proteomics analyses in gastric cancer cells treated with entinostat revealed a marked upregulation of EGFR in the majority of cell lines and an even more robust induction of the EGFR ligand AREG. This was confirmed in a panel of different cell lines in vitro, in tumor tissue-slice cultures ex vivo and in cell line- or patient-derived tumor xenografts in mice. Since previous studies in other tumor entities showed a downregulation of EGFR by HDACi, our findings thus indicate essential differences in the adaptive response of gastric carcinoma cells. Moreover, our results provided the basis for combined entinostat + EGFR inhibitor (erlotinib) treatment, and indeed we demonstrate synergistic effects in combination therapy studies. Conclusion: Our findings establish the profound upregulation of the EGFR/AREG axis by entinostat as starting point for a rational combination therapy in gastric carcinoma.